The Realistic of Mathematic Educational Approach to Enhancing Ability Mathematical Connections - Muhammad Hasbi; Agung Lukito; Raden Sulaiman (SAINTIS Publishing, 2019)
The aim of this study was to look at improving students' ability mathematical connection. Improve ability mathematical connection by developing Realistic Mathematics (RME) learning tools. This research is research and development, the results of this product are RPP, student activity sheets, teacher book guidelines, and student books. Development of learning tools based on a realistic approach developed using the 4-D development model from Thiagarajan. This research was conducted in grade VIII Junior High School 2 Candi Sidoarjo. The results of this study indicate: learning devices that are developed are valid, both in content validity and construction validity, there is an increase in ability mathematical connection of students using learning developed devices, and learning devices developed meet the criteria effectively, seen from: a) students' mathematical connection abilities are met , b) the ideal time of student activity is fulfilled, c) the teacher's performance in managing the class is fulfilled and d) the student's positive response.